Pengaruh Cyber Attack terhadap Kebijakan Cyber Security Amerika Serikat - Kristian Aji Nugroho; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This research aims to determine how the effect caused by cyber attack on cybersecuritypolicy in the United States This research is a descriptive study with guided by theframework of the concept of crime of caliber is a transnational crime by UNTOC, publicpolicy theory of Van Meter and Van Horn is a model of process of policy implementation,and constructivism caused by social interaction in society and international politicalculture make cybersecurity policy implemented in national and international scope. Thisresearch is a qualitative research using library research as a data source. The resultsobtained from the level of cyber attacks experienced by the United States affect the publicpolicy in the United States so that cybersecurity policy is made to maintain the securityand national sovereignty of the United States.